2013
DOI: 10.1364/oe.21.001804
|View full text |Cite
|
Sign up to set email alerts
|

Universal scaling of plasmonic refractive index sensors

Abstract: We establish experimental and numerical evidence that the refractive index sensitivities of various subwavelength plasmonic sensors obey a simple universal scaling relation that the sensitivities linearly increase with λm/neff (where λm is the resonant wavelengths and neff is the effective refractive index of the environment) and exhibit a slope equal to 1 instead of 2 predicted theoretically. The universal scaling relation is independent of the geometrical structures or contributions of multipolar resonances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The refractive index sensitivities of subwavelength structures (including SRRs, nanorods, and various kinds of nanoparticles) are generally described by either a standing wave model or Mie scattering theory. Recently, we find that the standing wave model is consistent with experimental and simulation results and yields a correct slope (ndλ m ∕λ m dn 1) of the universal scaling relation rather than 2, as predicted by the Mie scattering theory [2,6].…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The refractive index sensitivities of subwavelength structures (including SRRs, nanorods, and various kinds of nanoparticles) are generally described by either a standing wave model or Mie scattering theory. Recently, we find that the standing wave model is consistent with experimental and simulation results and yields a correct slope (ndλ m ∕λ m dn 1) of the universal scaling relation rather than 2, as predicted by the Mie scattering theory [2,6].…”
supporting
confidence: 80%
“…Because plasmonic resonant frequencies are sensitive to the environmental media, plasmonic nanostructures have been widely utilized for refractive index sensors. Recently, we have found that the refractive index sensitivities (dλ m ∕dn, where λ m is the resonant wavelengths of the mth harmonics, and n is the effective refractive index of the environment) for all kinds of individual or coupled plasmonic structures always linearly increase with λ m ∕n and exhibit a slope equal to 1 [2]. Moreover, the universal scaling relation is found to be independent of the geometries or harmonic modes of the metal structures.…”
mentioning
confidence: 98%
“…Metallic nanostructures provide new design and integration possibilities, which can lead to improvements in key SPR-based biosensor issues, such as sensitivity, resolution, multiplexing, and biological interfacing. Light transmission through subwavelength hole arrays has been extensively studied and discussed. Nanohole-array-based chemical and biological sensors offer numerous applications and display great performance, and recent progress has been focused on less-expensive fabrication methods. , SPR sensitivity to the dielectric materials in contact with the metal surface is the key for sensing applications, and it can be optically measured as refractive index (RI) changes reflected in spectral feature shifts or intensity variations …”
Section: Introductionmentioning
confidence: 99%
“…18−29 Nanohole-array-based chemical and biological sensors offer numerous applications and display great performance, 30−40 and recent progress has been focused on less-expensive fabrication methods. 41,42 SPR sensitivity to the dielectric materials in contact with the metal surface is the key for sensing applications, 43 and it can be optically measured as refractive index (RI) changes reflected in spectral feature shifts or intensity variations. 44 Noble metals such as gold and silver are used in the fabrication of the vast majority of nanohole-array SPR devices, 45,46 because of their very low resistivity, translated into low optical losses in the visible and near-infrared ranges.…”
Section: ■ Introductionmentioning
confidence: 99%